2020
DOI: 10.3389/fonc.2020.00500
|View full text |Cite
|
Sign up to set email alerts
|

Value of Pretreatment 18F-fluorodeoxyglucose Positron Emission Tomography in Patients With Localized Pancreatic Cancer Treated With Neoadjuvant Therapy

Abstract: Background: 18 F-fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) imaging is not routine in patients with localized pancreatic cancer (PC). We evaluated the prognostic value of PET/CT in patients who received neoadjuvant therapy. Methods: Patients with localized PC underwent pretreatment PET/CT with or without posttreatment (preop) PET/CT. Maximum standardized uptake values (SUV) were classified as high or low based on a cut point of 7.5 at diagnosis (SUV dx) and 3.5 after neoadjuva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Therefore, it is useful for considering the possibility of distant metastases in patients with resectable PDAC. 31,[38][39][40]…”
Section: F-fluorodeoxyglucose-positron Emission Tomographymentioning
confidence: 99%
“…Therefore, it is useful for considering the possibility of distant metastases in patients with resectable PDAC. 31,[38][39][40]…”
Section: F-fluorodeoxyglucose-positron Emission Tomographymentioning
confidence: 99%
“…Some authors wrote that patients with higher baseline (pre-CRT) SUVs were associated with a better response to therapy [ 8 ], and a better overall survival (OS) [ 14 ]. SUVs remaining high after neoadjuvant therapy correlated with a poor prognosis [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Associating changes in SUV max with other PET measurements—such as metabolic tumor volume (MTV), total lesion glycolysis (TLG) or SUL peak —could improve the prediction of response to treatment and OS [ 18 ]. Barnes et al [ 14 ] found that PET data in association with carbohydrate antigen 19–9 (CA 19–9) levels could significantly predict outcome and response to CRT, though Panda et al [ 18 ] reported that CA 19–9 levels showed some limitations in predicting OS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the sample size of the above studies was relatively small (< 50 cases in 2/3 articles), and the results were not convincing. Barnes et al [ 55 ] enrolled 201 consecutive patients with localized PDAC treated with NAT. The results showed that the pre-treatment SUVmax cut-off value of 7.5 on PET/CT could accurately predict the OS.…”
Section: Response Assessment Of Pdac After Natmentioning
confidence: 99%